Characterization of Ebinur Lake Virus and Its Human Seroprevalence at the China–Kazakhstan Border - Xia, Han; Liu, Ran; Zhao, Lu; Sun, Xiang; Zheng, Zhong; Atoni, Evans; Hu, Xiaomin; Zhang, Bo; Zhang, Guilin; Yuan, Zhiming (Frontiers in Microbiology, 2020)
In recent years, rapidly increasing trade and travel across the China-Kazakhstan border has increased the potential risk of the introduction and exportation of vectors and their related diseases. The Ebinur Lake Nature Reserve is located in Xinjiang Uygur Autonomous Region, near the China-Kazakhstan border, with a suitable ecosystem for mosquito breeding. In our previous work, a novel Orthobunyavirus species named Ebinur Lake virus (EBIV) was isolated in the reserve. To gain insights into the potential risk of EBIV in this region, we conducted a study that aimed to clearly outline EBIV’s biological characteristics and its human seroprevalence in this region. Phylogenetically, the analysis of all three segments of EBIV demonstrated that it belongs to the genus Orthobunyavirus, which is clustered in the Bunyamwera serogroup. EBIV replicated efficiently and caused CPEs in vertebrate cells. The survival rates of the EBIV-challenged mice were 0% and 20% when inoculated with viral concentrations ≥ 104 PFU or equal to 102 PFU, respectively. For EBIV-infected mice, internal bleeding and pathological changes were observed. In addition, the overall IgM antibody (1:4 by IFA), IgG antibody (1:10 by IFA) and neutralizing antibody (90% PRNT) prevalence was 8.05%, 12.3% and 0.95%, respectively, in the studied residents. In summary, EBIV is a new member of the Bunyamwera serogroup and is able to competently infect cells derived from mosquitoes, rodents, monkeys or humans. Furthermore, EBIV caused severe disease and even death in challenged Kunming mice, and the antibodies against EBIV has been detected in local residents, indicated that the virus is a potential animal or human pathogen.